Prostate Cancer Incidence and Mortality in Barbados, West Indies. (23rd February 2011) - Hennis, Anselm J. M.; Hambleton, Ian R.; Wu, Suh-Yuh; Skeete, Desiree H.-A.; Nemesure, Barbara; Leske, M. Cristina
Abstract : We describe prostate cancer incidence and mortality in Barbados, West Indies. We ascertained all histologically confirmed cases of prostate cancer during the period July 2002 to December 2008 and reviewed each death registration citing prostate cancer over a 14-year period commencing January 1995. There were 1101 new cases for an incidence rate of 160.4 (95% Confidence Interval: 151.0–170.2) per 100, 000 standardized to the US population. Comparable rates in African-American and White American men were 248.2 (95% CI: 246.0–250.5) and 158.0 (95% CI: 157.5–158.6) per 100, 000, respectively. Prostate cancer mortality rates in Barbados ranged from 63.2 to 101.6 per 100, 000, compared to 51.1 to 78.8 per 100, 000 among African Americans. Prostate cancer risks are lower in Caribbean-origin populations than previously believed, while mortality rates appeared to be higher than reported in African-American men. Studies in Caribbean populations may assist understanding of disparities among African-origin populations with shared heredity.